Entrepreneurship as a sustainable approach towards efficient waste management in Cairo - Estephanous, John (AUC Knowledge Fountain, 2015)
Despite the many trials of the government to solve the waste problem, and various research papers analyzing the problem and arguing the economic value of waste, however the waste sector has always been an untapped area for economic development, although it has potential for growth and benefit for many stakeholders. Through the last few years, the city of Cairo problems including the waste problem increased to an excessive level reflecting a problem with the management and control of the current waste management system. Moreover, when thinking of why Cairo have a persisting problem and about a better working new system, sustainability, entrepreneurship and innovation are very important aspects in devising a new framework for understanding the current, and building a different better future. Although there were many researches that predicted the problems and many others that gave recommendations for solutions. The gap between the information available about the problems and actions taken to solve while the problems persist, raise many questions about the practicality of the practiced reform policies and the ways policies are being drafted and taken to action in Egypt, and how it can be turned into sensed positive change. In addition to the inequality in the urban development and greater effect of the problems the city suffer from on the lower socioeconomic class of the population, that lead to their suffering from many other problems such as health problems and structural poverty. The degradation in the waste management as a problem has reached to a level where the city cannot endure anymore, if we are expecting a city to be a resilient and sustainable one for its inhabitants. Cairo is the country’s capital of which there is all the focus on its economic and touristic activities, and the waste accumulation is affecting the health of Cairo’s inhabitants as well as all the other functions of the city’s elements.Through all challenges that face the country, a trend can be sensed with the current political and social changes in Egypt, that the government is starting to shift towards more regulation than execution, where it seems clearer now, that the government cannot solve all problems on its own and at the same time monitor its execution. In addition to, finding better working solutions and practices to execute efficiently and solve problems by the government itself. Increased public participation in decision-making and delegation of problem solving to investors or public partners that can provide actions and support in many sectors started to seem as the solution. This can be seen in the new policies at the energy sector and the public-private partnerships on many projects that tackle services and new projects, and the creation of a new Ministry of Urban Renewal and Informal Settlements. The role of entrepreneurship in cities like Cairo can be the practical solution to its problems, when entrepreneurship can see challenges as opportunities for growth and making business by solving problems, and sustainability can drive the values of entrepreneurship into green business practices that take into consideration environmental and social aspects. Understanding the values of supporting entrepreneurship and building awareness and skills to support entrepreneurship development in Egypt is necessary now, and the challenge in creating entrepreneurship opportunities and making it sustainable, is deepened by the fact that in the neediest communities to entrepreneurship, are the least who have skills or education or money to grow and develop their businesses.